Antihyperlipidemic Effect Of Protocatechuic Acid In Fructose Induced Hyperlipidemia In Rats - ABHIJEET R BORATE,; ANUPAMA A SURALKAR,; SMITA S BIRJE,; PRAVIN V MALUSARE,; PRITAM A BANGALE, (International Journal of Pharma and Bio Sciences, 2011)
Hyperlipidemia is an abnormally high level of fatty substances called lipids, largely cholesterol and triglycerides, in the blood. Currently available hypolipidemic drugs have been associated with number of side effects. Herbal treatment for hyperlipidemia has fewer side effects. Protocatechuic acid (PCA), which is predominantly present in the flowers of Hibiscus sabdariffa, possesses antihyperlipidemic and free radical scavenging activity. Taking this into consideration PCA at the dose of 25 and 50 mg/kg were evaluated against fructose induced hyperlipidemia in rats and it has showed a significant decrease (p<0.05, p<0.01 respectively) in the levels of serum TC, TG and LDL and HDL was significantly increased (p<0.05, p<0.01 respectively) in serum when compared to fructose control group. Thus Protocatechuic acid has anti-hyperlipidemic activity which may be due to increased uptake of LDL cholesterol by hepatic LDL receptor or may be due to its effect on enzymes involved in metabolism and excretion of cholesterol.